Fluorite type high-entropy oxide supported nickel catalyst as well as preparation method and application thereof
By using fluorite-type high-entropy oxide as a support and preparing nickel catalysts by citric acid complexation and high-temperature calcination, the existing catalysts have been solved, and efficient CO2 methanation reaction has been achieved.
Patent Information
- Application Number
- CN202411678316.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-11
AI Technical Summary
The existing CO2 methanation catalyst has low activity and poor stability, making it difficult to achieve excellent CO2 conversion and CH4 selectivity.
The fluorite-type high-entropy oxide was used as the support and the nickel was evenly dispersed by a one-step method of citric acid complexing, combined with high-temperature calcination and reduction treatment, and a high-dispersion and low-sintering nickel catalyst was prepared.
The catalyst has high catalytic activity and good stability, the CO2 conversion rate can reach more than 90%, the CH4 selectivity reaches 99%, and the stability of 100 hours is maintained at a reaction temperature of 500°C.
Smart Images

Figure CN119793473A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to an oxide-supported nickel catalyst and a preparation method and application thereof. Background Art
[0002] High entropy oxides (HEOs) belong to the emerging high entropy materials (HEMs) in recent years, and have shown research value in thermal catalysis, photocatalysis, electrocatalysis, and as carriers. Specifically, high entropy oxides (HEOs) refer to five or more quasi-molecular metal elements arranged in an orderly manner in a randomly distributed single-phase lattice, and the structure is stabilized by increasing the configuration entropy of the system (Sconfig ≥ 1.61R). After forming a single-phase HEOS with a cubic or hexagonal lattice, higher temperature treatment (such as > 1000 ° C) can hardly destroy the structure, so it has excellent thermal stability and can provide support for high-temperature catalytic reactions. Existing high entropy oxides include a variety of three-dimensional structures such as rock salt, spinel, fluorite, perovskite and solid solution, which are different from traditional composite oxides, so they have broader development and application prospects.
[0003] In view of the many problems of energy shortage and environmental pollution currently faced, the CH4 and CO produced by methanation and reverse water gas shift reaction using CO2 and H2 as raw materials can further expand the utilization value, achieve the dual carbon goals in a green and safe way, and contribute to CO2 capture and utilization (CCU). CH4 after CO2 conversion can be used as a safe fuel, or it can be further reacted to obtain hydrocarbons; and the CO obtained from CO2 through reverse water gas shift is an important component of synthesis gas, which can be converted into methanol, formic acid, dimethyl ether and other organic high-added products through various channels. CO2 hydrogenation is also helpful in the energy storage level. It can solve the hydrogen storage problem after hydrogen production by water electrolysis, and can also improve the problem of renewable energy fluctuations. In general, CO2 hydrogenation can not only alleviate energy pressure, but also achieve dual carbon goals. The development potential of CO2 hydrogenation reaction catalysts is huge and the prospects are bright.
[0004] The catalysts reported for the CO2 methanation reaction (CO2+4H2=CH4+2H2O) are mainly supported metal catalysts based on active metals such as Ni, Ru, Rh, and Co. The catalysts with these active metal components all show excellent CO2 conversion and CH4 selectivity; but in comparison, the upper limit of the activity of Ru and Rh-based precious metal catalysts is higher than that of metal catalysts such as Ni and Co. Their CH4 selectivity can often reach 100%, and their CO2 conversion rate can also be above 90%. The activity is extremely excellent, but the cost is too high, making it difficult to achieve industrial application, and the preparation technology needs to be improved; Ni and Co-based catalysts are relatively low in cost and have broad prospects for industrial application, but their catalytic activity needs to be further improved. In addition, due to the exothermic characteristics of CO2 methanation, the above-mentioned supported active metal catalysts all face the problems of low thermal stability and sintering of active metals.
[0005] At present, the carrier for active metal Ni is usually a single metal oxide, such as Al2O3, ZrO2, etc. These metal oxides can achieve a certain degree of activity, selectivity or stability as carriers, but are limited by the characteristics of a single type of metal oxide, and it is often difficult to achieve the overall excellent performance of CO2 methanation. In addition, the Ni catalyst loaded with other types of metal oxides doped on a single metal oxide also has mediocre performance in one or two indicators of CO2 methanation activity, selectivity and stability. Therefore, considering the natural excellent thermal stability of high entropy oxides due to high configurational entropy and the unexpected "cocktail" effect produced by the mixed composition of multiple metals, the use of high entropy oxides as carriers to load active metal Ni has become a feasible way to achieve excellent performance in CO2 methanation and ensure high dispersion and low sintering of active metal Ni, and has broad application prospects. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of low activity and poor stability of existing CO2 methanation catalysts, and to use fluorite-type high entropy oxides as catalyst carriers. The present invention has the following characteristics: (1) utilizing the excellent thermal stability of high entropy oxides, the CO2 methanation strongly exothermic reaction and the reaction characteristics under high temperature conditions can maintain structural stability and achieve excellent stability; (2) using a one-step method of citric acid complexation to uniformly disperse the active component nickel in the mixed oxide, achieve high dispersion of nickel, and thus achieve excellent activity; (3) the combination of high entropy oxides and metallic nickel exhibits high methane selectivity.
[0007] According to one aspect of the present invention, a fluorite-type high-entropy oxide-supported nickel catalyst is provided, comprising a fluorite-type high-entropy oxide, wherein the fluorite-type high-entropy oxide is loaded with metallic nickel; the molecular formula of the fluorite-type high-entropy oxide is expressed as AO2, A is an ion of five transition metal elements, Ce, Zr, Y, La, and Ti, and the five transition metal elements have equimolar contents; the configuration entropy S of the fluorite-type high-entropy oxide is config ≥1.61R.
[0008] Furthermore, the nickel content of the fluorite-type high-entropy oxide is 5% to 20%, calculated based on the mass content of metallic nickel in the catalyst.
[0009] According to another aspect of the present invention, there is provided a method for preparing a fluorite-type high entropy oxide-supported nickel catalyst, comprising the following steps:
[0010] (1) dissolving a metal nitrate containing a type A element, nickel nitrate, citric acid, and ethylene glycol in deionized water to obtain a mixed solution;
[0011] (2) stirring the mixed solution obtained in step (1) in a water bath at 60-100° C. with magnetic force until a gel is obtained, and then drying to obtain a xerogel;
[0012] (3) calcining the dry gel obtained in step (2) at 300-400° C. for 1-3 h, and then heating to 750-850° C. for calcining for 2-6 h; after cooling, reducing the product at 600-750° C. in a reducing atmosphere for 2 h to obtain a fluorite-type high entropy oxide-supported nickel catalyst.
[0013] Furthermore, in step (1), the metal nitrate containing type A elements is composed of cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, and tetrabutyl titanate.
[0014] Furthermore, in step (1), the molar ratio of the total amount of the metal nitrate containing the A-type element and the nickel nitrate, the citric acid, and the ethylene glycol is 1:(1-2):(0.2-1).
[0015] Furthermore, in step (2), the drying temperature is 80-120° C., and the drying time is 8-16 h.
[0016] Furthermore, in step (3), the heating rates of the two heating steps are 1-5°C / min.
[0017] According to another aspect of the present invention, the above-mentioned fluorite-type high entropy oxide-supported nickel catalyst is provided for use in carbon dioxide methanation reaction.
[0018] Furthermore, the reducing atmosphere is an inert gas, hydrogen or a mixed gas atmosphere of inert gas and hydrogen, and the reduction treatment time is 1-3 hours.
[0019] Further, as a catalyst, the catalyst is added to the reactor at a temperature of 400-550°C and a pressure of 1-5 MPa at a volume space velocity of 6000-24000 mL / (g cat h) introducing carbon dioxide and hydrogen, wherein the molar ratio of carbon dioxide to hydrogen is 1:(3-4).
[0020] The beneficial effects of the present invention are:
[0021] (i) The fluorite-type high-entropy oxide provided by the present invention adopts five equimolar metal components, achieving the expected purpose of high configurational entropy, ensuring that the high-entropy oxide carrier has good stability, and at the same time, the high-entropy oxide carrier achieves high dispersion of the loaded active metal Ni, which helps to achieve high catalytic activity of the catalyst;
[0022] (ii) The fluorite-type high entropy oxide provided by the present invention is prepared by citric acid complexation combined with high-temperature calcination. Overall, the preparation method has a clear principle, is easy to use and easy to operate, and is suitable for subsequent large-scale promotion;
[0023] (III) The present invention utilizes the good high-temperature stability of high-entropy fluorite oxide, the defects and oxygen vacancies that can be formed on the surface, the synergistic redox effect of multiple metal ions, and the good dispersibility and thermal stability of the loaded metal nickel ions, and applies it to the methanation reaction, thereby avoiding the aggregation of active metal ions from the structural point of view and having good activity; after the prepared high-entropy fluorite oxide is reduced, only the active metal Ni will participate in the reduction, while the other component metals jointly construct the fluorite structure, which serves as a carrier of the active metal Ni, and achieves excellent CO2 methanation activity. Specifically, the CO2 conversion rate can reach more than 90%, the CH4 selectivity can reach 99%, and the stability can achieve a 100-h test at a reaction temperature of 500°C, which has considerable prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the XRD diagram of the catalysts prepared in Examples 2, 5, 8, 11 and 14 of the present invention after calcination.
[0025] Figure 2 It is the XRD diagram of the catalysts prepared in Examples 2, 5, 8, 11 and 14 of the present invention after reduction.
[0026] Figure 3 It is the XRD diagram of the catalysts prepared in Examples 2, 5, 8, 11 and 14 of the present invention after reaction.
[0027] Figure 4 This is a CO2 methanation performance diagram of the catalysts prepared in Examples 2, 5, 8, 11, and 14 of the present invention.
[0028] Figure 5 This is a CO2 methanation performance diagram of the catalysts prepared in Examples 8, 17, 20, 23, and 26 of the present invention when calcined at different temperatures.
[0029] Figure 6 It is the XRD pattern of the catalyst prepared in Examples 16-27 of the present invention after calcination.
[0030] Figure 7 This is the XRD diagram of the catalysts prepared in Examples 16-27 of the present invention after reduction.
[0031] Figure 8 This is the XRD diagram of the catalysts prepared in Examples 16-27 of the present invention after reaction.
[0032] Fig. 9 This is the XRD diagram of the catalyst prepared in Example 28 of the present invention before and after stability.
[0033] Fig.10 This is a 100h stability test chart of the catalyst prepared in Example 28 of the present invention.
[0034] Fig.11 This is the XRD diagram of the catalyst prepared in Example 29 of the present invention before and after stability. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0036] Example 1
[0037] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.2:0.2:0.2:0.2:0.2:1:0.2.
[0038] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0039] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1 h, and then continued to be heated to 750°C and calcined for 2 h to obtain catalyst Ce. 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O2-750.
[0040] 4) 0.2 g of the catalyst was added to the fixed bed reactor, and the fixed bed reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO2 conversion rate was 40.7%, and CH4 selectivity was 0%.
[0041] Example 2
[0042] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.2:0.2:0.2:0.2:0.2:1.2:0.2.
[0043] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0044] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, and then continued to be heated to 750°C and calcined for 4h to obtain catalyst Ce 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O2-750.
[0045] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 17.8%, and CH4 selectivity was 0%.
[0046] Example 3
[0047] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.2:0.2:0.2:0.2:0.2:2:0.4.
[0048] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0049] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, and then continued to be heated to 750°C and calcined for 6h to obtain catalyst Ce. 0.2 Zr 0.2 Y 0.2 La 0.2 Ti 0.2 O2-750.
[0050] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 41.2%, and CH4 selectivity was 0%.
[0051] Example 4
[0052] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.183:0.183:0.183:0.183:0.183:0.08:1:0.2.
[0053] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0054] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, then continued to be heated to 750°C and calcined for 2h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 5% Ni / (CeZrYLaTi) 0.2 O2-750.
[0055] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500 °C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 6000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 73.9%, and CH4 selectivity was 91.4%.
[0056] Example 5
[0057] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.183:0.183:0.183:0.183:0.183:0.08:1.2:0.2.
[0058] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0059] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 750°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 5% Ni / (CeZrYLaTi) 0.2 O2-750.
[0060] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 75.2%, and CH4 selectivity was 93.6%.
[0061] Example 6
[0062] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.183:0.183:0.183:0.183:0.183:0.08:1:0.2.
[0063] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0064] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, then continued to be heated to 750°C and calcined for 6h. After cooling, the product was reduced in a hydrogen atmosphere at 750°C for 2h to obtain a catalyst 5% Ni / (CeZrYLaTi) 0.2 O2-750.
[0065] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO2 conversion rate was 74.3%, and CH4 selectivity was 92.0%.
[0066] Example 7
[0067] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1:0.2.
[0068] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0069] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, then continued to be heated to 750°C and calcined for 2h. After cooling, the product was reduced in a hydrogen atmosphere at 600°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2-750.
[0070] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO2 conversion rate was 91.2%, and CH4 selectivity was 97.9%.
[0071] Example 8
[0072] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1.2:0.2.
[0073] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0074] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 750°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2-750.
[0075] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 92.0%, and CH4 selectivity was 99.3%.
[0076] Example 9
[0077] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1:0.2.
[0078] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0079] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, then continued to be heated to 750°C and calcined for 6h. After cooling, the product was reduced in a hydrogen atmosphere at 750°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2-750.
[0080] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500 °C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 90.8%, and CH4 selectivity was 98.3%.
[0081] Example 10
[0082] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.153:0.153:0.153:0.153:0.153:0.235:1:0.2.
[0083] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0084] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, then continued to be heated to 750°C and calcined for 2h. After cooling, the product was reduced in a hydrogen atmosphere at 600°C for 2h to obtain a catalyst 15% Ni / (CeZrYLaTi) 0.2 O2-750.
[0085] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO2 conversion rate was 89.3%, and CH4 selectivity was 98.1%.
[0086] Embodiment 11
[0087] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.153:0.153:0.153:0.153:0.153:0.235:1.2:0.2.
[0088] 2) Stir and evaporate the prepared salt solution in a water bath at 80°C, and dry in an oven at 120°C for 10 hours.
[0089] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 750°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 15% Ni / (CeZrYLaTi) 0.2 O2-750.
[0090] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 90.0%, and CH4 selectivity was 99.3%.
[0091] Example 12
[0092] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.153:0.153:0.153:0.153:0.153:0.235:2:0.4.
[0093] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0094] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, then continued to be heated to 750°C and calcined for 6h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 15% Ni / (CeZrYLaTi) 0.2 O2-750.
[0095] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 400 °C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 82.4%, and CH4 selectivity was 98.3%.
[0096] Example 13
[0097] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.139:0.139:0.139:0.139:0.139:0.304:1:0.2.
[0098] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0099] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, then continued to be heated to 750°C and calcined for 2h. After cooling, the product was reduced in a hydrogen atmosphere at 600°C for 2h to obtain a catalyst 20% Ni / (CeZrYLaTi) 0.2 O2-750.
[0100] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 400°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 89.2%, and CH4 selectivity was 99.1%.
[0101] Embodiment 14
[0102] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.139:0.139:0.139:0.139:0.139:0.304:1.2:0.2.
[0103] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0104] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 750°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 20% Ni / (CeZrYLaTi) 0.2 O2-750.
[0105] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 93.1%, and CH4 selectivity was 99.4%.
[0106] Embodiment 15
[0107] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.139:0.139:0.139:0.139:0.139:0.304:2:0.4.
[0108] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0109] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, then continued to be heated to 750°C and calcined for 6h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 20% Ni / (CeZrYLaTi) 0.2 O2 -750.
[0110] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 89.2%, and CH4 selectivity was 97.9%.
[0111] Example 16
[0112] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1:0.2.
[0113] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0114] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, then continued to be heated to 550°C and calcined for 2h. After cooling, the product was reduced in a hydrogen atmosphere at 680°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -550.
[0115] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 400 °C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 24000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 90.5%, and CH4 selectivity was 99.4%.
[0116] Embodiment 17
[0117] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1.2:0.2.
[0118] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0119] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 550°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2O2 -550.
[0120] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 92.6%, and CH4 selectivity was 99.3%.
[0121] Embodiment 18
[0122] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:2:0.4.
[0123] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0124] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, then continued to be heated to 550°C and calcined for 6h. After cooling, the product was reduced at 750°C in a hydrogen atmosphere for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -550.
[0125] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 6000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 91.3%, and CH4 selectivity was 98.6%.
[0126] Embodiment 19
[0127] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1:0.2.
[0128] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0129] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, then continued to be heated to 650°C and calcined for 2h. After cooling, the product was reduced in a hydrogen atmosphere at 600°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi)0.2 O2 -650.
[0130] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 400°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO2 conversion rate was 91.0%, and CH4 selectivity was 99.3%.
[0131] Embodiment 20
[0132] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1.2:0.2.
[0133] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0134] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 650°C and calcined for 4h. After cooling, the product was reduced at 700°C in a hydrogen atmosphere for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -650.
[0135] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 93.5%, and CH4 selectivity was 99.5%.
[0136] Embodiment 21
[0137] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:2:0.4.
[0138] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0139] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, then continued to be heated to 650°C and calcined for 6h. After cooling, the product was reduced in a hydrogen atmosphere at 720°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -650.
[0140] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO2 conversion rate was 91.7%, and CH4 selectivity was 98.8%.
[0141] Embodiment 22
[0142] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1:0.2.
[0143] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0144] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, then continued to be heated to 850°C and calcined for 2h. After cooling, the product was reduced in a hydrogen atmosphere at 600°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -850.
[0145] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 450°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 84.5%, and CH4 selectivity was 98.5%.
[0146] Embodiment 23
[0147] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1.2:0.2.
[0148] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0149] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 850°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -850.
[0150] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 88.9%, and CH4 selectivity was 98.8%.
[0151] Embodiment 24
[0152] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:2:0.4.
[0153] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0154] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, then continued to be heated to 850°C and calcined for 6h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -850.
[0155] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 6000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 85.1%, and CH4 selectivity was 96.6%.
[0156] Embodiment 25
[0157] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1:0.2.
[0158] 2) Stir and evaporate the prepared salt solution in a 60°C water bath and dry in an oven at 80°C for 8 hours.
[0159] 3) The dried product was heated to 300°C at 1°C / min and calcined for 1h, then continued to be heated to 950°C and calcined for 2h. After cooling, the product was reduced in a hydrogen atmosphere at 600°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -950.
[0160] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 450°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. Test results: CO2 conversion rate was 89.0%, and CH4 selectivity was 99.1%.
[0161] Embodiment 26
[0162] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.168:0.168:0.168:0.168:0.168:0.162:1.2:0.2.
[0163] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0164] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 950°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -950.
[0165] 4) Test results: 0.2 g of catalyst was added to the reactor, and at a temperature of 500 ° C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:4. The CO2 conversion rate was 87.9% and the CH4 selectivity was 99.0%.
[0166] Embodiment 27
[0167] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:2:0.4.
[0168] 2) The prepared salt solution was stirred and evaporated in a 100°C water bath and dried in an oven at 120°C for 16 hours.
[0169] 3) The dried product was heated to 400°C at 5°C / min and calcined for 3h, then continued to be heated to 950°C and calcined for 6h. After cooling, the product was reduced at 700°C in a hydrogen atmosphere for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -950.
[0170] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 550°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was conducted by introducing carbon dioxide and hydrogen at a molar ratio of 1:3. Test results: CO2 conversion rate was 89.7%, and CH4 selectivity was 98.4%.
[0171] Embodiment 28
[0172] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1.2:0.2.
[0173] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0174] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 550°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -550.
[0175] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) The stability test of CO2 methanation was carried out by introducing carbon dioxide and hydrogen in a molar ratio of 1:4.
[0176] Embodiment 29
[0177] 1) Cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate, tetrabutyl titanate, nickel nitrate, citric acid and ethylene glycol are prepared into a mixed salt solution with a molar ratio of 0.:168:0.168:0.168:0.168:0.168:0.162:1.2:0.2.
[0178] 2) The prepared salt solution was stirred and evaporated in a water bath at 80°C and dried in an oven at 120°C for 12 hours.
[0179] 3) The dried product was heated to 350°C at 2°C / min and calcined for 2h, then continued to be heated to 850°C and calcined for 4h. After cooling, the product was reduced in a hydrogen atmosphere at 700°C for 2h to obtain a catalyst 10% Ni / (CeZrYLaTi) 0.2 O2 -850.
[0180] 4) 0.2 g of catalyst was added to the reactor, and at a temperature of 500°C and a pressure of 3 MPa, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) The stability test of CO2 methanation was carried out by introducing carbon dioxide and hydrogen in a molar ratio of 1:4.
[0181] During the 100-hour stability test, the CO2 conversion rate was maintained at 81.5%, and the CH4 selectivity was maintained at 99.0%, with good thermal stability.
[0182] The products of step 3) and step 4) of Examples 2, 5, 8, 11, and 14 of the present invention were subjected to XRD analysis respectively, and the XRD patterns of the catalysts after calcination, reduction, and reaction were respectively Figure 1 , Figure 2 , Figure 3 .from Figure 1 It can be seen that the catalyst prepared in Example 2 calcined at 750°C forms a fluorite structure; Figure 2 , Figure 3 It can be seen that the fluorite structure of the catalyst prepared in Example 2 remains good after the reaction, that is, the fluorite structure remains consistent before and after the reaction, and the thermal stability is good. Figure 1 It can be seen that the catalysts prepared by Examples 5, 8, 11, and 14 calcined at 750°C formed fluorite structure and NiO characteristic peaks, and NiO had good dispersion. Figure 2 , Figure 3 It can be seen that after the catalysts prepared in Examples 5, 8, 11, and 14 are reduced, the NiO phase disappears and the Ni characteristic peak appears. After the reaction, the Ni characteristic peak and the fluorite structure are both good, that is, the reduced Ni phase is highly dispersed and has good anti-sintering performance. The fluorite structure also remains consistent before and after the reaction and has good thermal stability.
[0183] 0.2 g of the product after step 3) of Examples 2, 5, 8, 11, and 14 of the present invention was taken for CO2 methanation performance test. The reaction pressure was 3 MPa and the reaction temperature was 300-550°C. The reaction gas composition was analyzed by gas chromatography. The corresponding CO2 conversion rate and CH4 selectivity data were calculated based on the carbon balance principle and the test data. Figure 4 .from Figure 4 It can be seen that as the Ni loading mass fraction increases from 5% to 20%, the CO2 conversion rate gradually increases. The CO2 conversion rate of the catalysts with a Ni loading of 10%, 15%, and 20% is low in the lower temperature range of 300-350°C. This is because CO2 methanation is an exothermic reaction, and high temperature is more conducive to the reaction. In the range of 400-550°C, the CO2 conversion rate level remains above 80%, and at the same time, it can have 100% CH4 selectivity and excellent activity. Among the catalysts with a Ni loading of 10%, 15%, and 20%, 10% Ni / (CeZrYLaTi) 0.2 O x -750 catalyst has the best overall performance.
[0184] 0.2 g of the product after step 3) of Examples 8, 17, 20, 23, and 26 of the present invention was taken for CO2 methanation performance test, i.e., the reaction pressure was 3 MPa, the reaction temperature was 300-550°C, the reaction gas composition was analyzed by gas chromatography, and the corresponding CO2 conversion rate and CH4 selectivity data were calculated based on the carbon balance principle combined with the test data to obtain Figure 5 .from Figure 5 It can be seen that: overall, the CO2 conversion rate is better for catalysts prepared at low temperatures. Since CO2 methanation is an exothermic reaction, the catalytic activity in the low reaction temperature range of 300-350°C is average, while the CO2 conversion levels of catalysts prepared at five temperatures in the range of 400-550°C are basically above 80%; for CH4 selectivity, the catalysts prepared at low temperatures of 550°C and 650°C have ordinary CH4 selectivity in the low temperature range, while the catalysts prepared at high temperatures of 750°C, 850°C and 950°C can always maintain CH4 selectivity at 99% in the entire temperature range, with good selectivity. The CO2 conversion rate of the catalysts prepared at high temperatures of 750°C and 850°C is generally better than that of the catalysts prepared at 950°C in the temperature range of 400-550°C, and is not much different from that of the catalysts prepared at 550°C and 650°C, both of which are better than traditional single metal oxide-supported Ni catalysts; for CH4 selectivity, the catalysts prepared at 550-950°C are basically at the 99% level, with a high overall selectivity level; in general, the CO2 conversion rate and CH4 selectivity of the catalysts prepared at 750°C and 850°C are at excellent levels, that is, the activity performance is good.
[0185] The products of step 3) and step 4) of Examples 8, 17, 20, 23, and 26 of the present invention were subjected to XRD analysis respectively, and the XRD patterns of the fluorite-type high entropy oxide-supported nickel catalyst after calcination, reduction, and reaction were obtained. Figure 6 , Figure 7 , Figure 8 .from Figure 6It can be seen that the catalysts prepared in Examples 17 and 20 did not form a fluorite structure; Figure 7 It can be seen that the catalysts prepared in Examples 17 and 20 underwent a transformation from NiO phase to Ni phase after reduction, but still did not form a fluorite structure. Figure 8 It can be seen that the catalysts prepared in Examples 17 and 20 showed weak fluorite characteristic peaks after the reaction, indicating that the catalyst oxide carrier structure obtained by calcining at low temperatures of 550°C and 650°C was unstable and the expected thermal stability was poor. Figure 6 It can be seen that the catalysts prepared in Examples 8 and 23 formed a fluorite structure; Figure 7 , Figure 8 It can be seen that the fluorite structure of the catalysts prepared in Examples 8 and 23 remained good after the reaction, that is, the fluorite structure remained consistent before and after the reaction, indicating that the fluorite structure of the catalyst oxide carrier obtained by calcining at 750°C and 850°C was stable and had good expected thermal stability. Figure 6 It can be seen that the catalysts prepared in Examples 8 and 23 formed fluorite structure and NiO characteristic peaks, and NiO had good dispersion. Figure 7 , Figure 8 It can be seen that after the catalysts prepared in Examples 8 and 23 are reduced, the NiO phase disappears and the Ni characteristic peak appears. After the reaction, the Ni characteristic peak and the fluorite structure are both good, that is, the reduced Ni phase is highly dispersed and has good anti-sintering performance. The fluorite structure is also consistent before and after the reaction and has good thermal stability. Figure 6 It can be seen that the catalyst prepared in Example 26 not only forms a fluorite structure, but also produces several non-fluorite characteristic peaks, that is, there are other phases besides the fluorite phase; Figure 8 It can be seen that after the catalyst prepared in Example 26 is reduced, the NiO phase disappears and the Ni phase appears. The Ni phase still exists after the reaction, that is, the Ni dispersion is good, but the impurity phases present in the high entropy oxide carrier exist both after reduction and after the reaction and do not disappear, indicating that the non-single fluorite phase structure of the catalyst oxide carrier obtained by calcining at 950°C is relatively unstable and the thermal stability is expected to be poor.
[0186] The products of step 3) and step 4) of Example 28 of the present invention were subjected to XRD analysis to obtain XRD spectra after catalyst reduction and stability reaction, as shown in FIG. Fig. 9 As shown. Fig. 9 It can be seen that the catalyst did not form a fluorite structure before the stability test, but formed a fluorite structure after the stability test. At the same time, the Ni characteristic peak became sharper and the Ni particles grew larger.
[0187] 0.2 g of the product after step 3) of Example 28 of the present invention was taken for CO2 methanation stability test, that is, the reaction pressure was 3 MPa, the reaction temperature was 400-550°C, and the reaction gas composition was analyzed by gas chromatography. The corresponding CO2 conversion rate and CH4 selectivity data were calculated based on the carbon balance principle and the test data, and the results were as follows: Fig.10 .Depend on Fig.10 It can be seen that the initial CO2 conversion rate of the reaction is 90.6%, and then reaches a maximum conversion rate of 92.7% within 12 hours. The CO2 conversion rate is relatively stable at 90.6% within 0 to 100 hours of stability. During the 100-hour stability test, the CH4 selectivity of the catalyst varies between 98.6% and 99.4%, with some fluctuations. Overall, the thermal stability of the low-temperature calcined catalyst is acceptable.
[0188] The products of step 3) and step 4) of Example 29 of the present invention were subjected to XRD analysis to obtain XRD patterns after catalyst reduction and stability reaction, as shown in FIG. Fig.11 As shown. Fig.11 It can be seen that the catalyst formed a fluorite structure and Ni characteristic peaks appeared before the stability test. After the stability test, the fluorite structure and Ni characteristic peaks still existed, that is, Ni was highly dispersed and had good anti-sintering performance. The fluorite structure could also remain stable, and the overall thermal stability was good.
[0189] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.
Claims
1. A fluorite-type high entropy oxide-supported nickel catalyst, characterized in that: The invention comprises a fluorite-type high entropy oxide, wherein the fluorite-type high entropy oxide is loaded with metal nickel; the molecular formula of the fluorite-type high entropy oxide is AO2, A is an ion of five transition metal elements, namely Ce, Zr, Y, La and Ti, and the five transition metal elements have an equimolar content; the configuration entropy S of the fluorite-type high entropy oxide is config ≥1.61R.
2. The fluorite-type high entropy oxide-supported nickel catalyst according to claim 1, characterized in that: The nickel content of the fluorite-type high-entropy oxide is 5% to 20%, calculated based on the mass content of metallic nickel in the catalyst.
3. A method for preparing a fluorite-type high entropy oxide-supported nickel catalyst as claimed in any one of claims 1 to 2, characterized in that: The process includes the following: (1) dissolving a metal nitrate containing a type A element, nickel nitrate, citric acid, and ethylene glycol in deionized water to obtain a mixed solution; (2) stirring the mixed solution obtained in step (1) in a water bath at 60-100° C. with magnetic force until a gel is obtained, and then drying to obtain a xerogel; (3) calcining the dry gel obtained in step (2) at 300-400° C. for 1-3 h, and then heating to 750-850° C. for calcining for 2-6 h; after cooling, reducing the product at 600-750° C. in a reducing atmosphere for 2 h to obtain a fluorite-type high entropy oxide-supported nickel catalyst.
4. The method for preparing a fluorite-type high entropy oxide-supported nickel catalyst according to claim 3, characterized in that: In step (1), the metal nitrate containing type A elements is composed of cerium nitrate, zirconium nitrate, yttrium nitrate, lanthanum nitrate and tetrabutyl titanate.
5. The method for preparing a fluorite-type high entropy oxide-supported nickel catalyst according to claim 3, characterized in that: In step (1), the molar ratio of the total amount of the metal nitrate containing the A-type element and the nickel nitrate, the citric acid, and the ethylene glycol is 1:(1-2):(0.2-1).
6. The method for preparing a fluorite-type high entropy oxide-supported nickel catalyst according to claim 3, characterized in that: In step (2), the drying temperature is 80-120° C. and the drying time is 8-16 hours.
7. The method for preparing a fluorite-type high entropy oxide-supported nickel catalyst according to claim 3, characterized in that: In step (3), the heating rates of the two heating steps are 1-5°C / min.
8. A fluorite-type high entropy oxide-supported nickel catalyst as claimed in any one of claims 1 to 2 for use in carbon dioxide methanation reaction.
9. The fluorite-type high entropy oxide-supported nickel catalyst for carbon dioxide methanation reaction according to claim 8, characterized in that: The reducing atmosphere is an inert gas, hydrogen or a mixed gas atmosphere of inert gas and hydrogen, and the reducing treatment time is 1-3 hours.
10. The fluorite-type high entropy oxide-supported nickel catalyst for carbon dioxide methanation reaction according to claim 8, characterized in that: As a catalyst, the reactor is charged with 2000-24000 mL / (g / min) of 1% tantalum at a temperature of 400-550°C and a pressure of 1-5 MPa. cat h) introducing carbon dioxide and hydrogen, wherein the molar ratio of carbon dioxide to hydrogen is 1:(3-4).